Triumphs of Experience : the Men of the Harvard Grant Study - Vaillant, George E., 1934- (Belknap Press of Harvard University Press, 2012)
At a time when people are living into their tenth decade, the longest longitudinal study of human development ever undertaken offers welcome news for old age: our lives evolve in our later years and often become more fulfilling. Reporting on all aspects of male life Triumphs of Experience shares a number of surprising findings.